(untitled) (Scientific journal of the Fergana State University, 2023)
This article is devoted to the analysis and interpretation of the skill of creating a national hero in recent years in prose, in particular in the story "Faryod" by Jizzakh writer Abdullah Ahmad. The article presents the plot of the writer’s methodological research on the example of the story, the description of the tragic events experienced by the protagonists.